2010
DOI: 10.1309/ajcpfahvb26vvvte
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Carbamazepine and Carbamazepine-10,11-Epoxide Concentrations in Plasma Using Mathematical Equations Generated With Two Carbamazepine Immunoassays

Abstract: Carbamazepine is metabolized to an active metabolite known as carbamazepine-10,11-epoxide, or simply the "epoxide" metabolite. The presence of this metabolite can have clinically significant implications in therapeutic drug monitoring of carbamazepine, but accurate quantification of the epoxide metabolite is currently limited to chromatographic techniques. In this study, mathematical equations are proposed for the estimation of carbamazepine and epoxide metabolite concentrations based on values generated by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…These results were consistent with the report that antibodies for these two drugs showed cross‐reactivity with their metabolites (Neels et al ., ). Since the PETINIA method was reported to show a high level of cross‐reactivity for carbamazepine‐10,11‐epoxide (McMillin et al ., ), we compared the sum of carbamazepine and its epoxide concentrations determined by the UPLC‐MS/MS method with carbamazepine concentrations determined by this immunoassay. However, the sum was still smaller than the immunoassay values; this indicates that the antibody for carbamazepine may have cross‐reacted not only with carbamazepine‐10,11‐epoxide but also with its other metabolites.…”
Section: Resultsmentioning
confidence: 99%
“…These results were consistent with the report that antibodies for these two drugs showed cross‐reactivity with their metabolites (Neels et al ., ). Since the PETINIA method was reported to show a high level of cross‐reactivity for carbamazepine‐10,11‐epoxide (McMillin et al ., ), we compared the sum of carbamazepine and its epoxide concentrations determined by the UPLC‐MS/MS method with carbamazepine concentrations determined by this immunoassay. However, the sum was still smaller than the immunoassay values; this indicates that the antibody for carbamazepine may have cross‐reacted not only with carbamazepine‐10,11‐epoxide but also with its other metabolites.…”
Section: Resultsmentioning
confidence: 99%
“…In one case immunoassays were used to generate mathematical equations for determination of carbamazepine and its metabolite in plasma (19). Tables 2 to 5 Results for accuracy are presented as minimum and maximum values obtained for inter-day and intra-day, where applicable.…”
Section: Bioanalytical Methods For Determination Of Carbamazepine Andmentioning
confidence: 99%
“…The authors observed a good correlation between epoxide concentrations obtained by using mathematical equations with true epode concentrations determined by LC/MS/MS(24) . After calculating the value of y , value of x can be easily determined.…”
mentioning
confidence: 86%